Relationship Between Low Birth Weight and Neonatal Asphyxia Incidence at Kalabahi-Alor Regional Hospital in the 2021-2024 Period - Calistha Regina Sandy; Gottfrieda P. Taeng Ob-Adang; Nicholas Edwin Handoyo; Deif Tunggal (Jurnal Biologi Tropis, 2026)
Neonatal mortality is still a worldwide issue. Two of the main reasons for new-born deaths, including those at Kalabahi-Alor Regional Hospital, are neonatal asphyxia and low birth weight. It is vital to comprehend how low birth weight is connected to asphyxia to implement preventive measures. This research intends to examine the connection between low birth weight and the occurrence of asphyxia in newborns at Kalabahi-Alor Regional Hospital from 2021 to 2024 after adjusting for other risk factors. The study employs an analytical observational design with a descriptive method. It is a case-control retrospective research. The data analysis comprises univariate, bivariate (Chi-Square), and multivariate (logistic regression) to pinpoint independent risk factors. The bivariate analysis indicates that low birth weight significantly correlates with the occurrence of asphyxia (p-value 0.004), along with prematurity (p-value 0.044). Additionally, the multivariate analysis results revealed that low birth weight is an independent predictor of asphyxia occurrence after accounting for the variables of primiparity and prematurity with a p-value of 0.031 and odds ratio of 5.426, which shows that newborns with low birth weight are over five times more likely to face asphyxia compared to those with normal birth weight. In conclusion, there is a significant correlation between low birth weight and the incidence of neonatal asphyxia at Kalabahi-Alor Regional Hospital from 2021 to 2024 after other risk factors have been taken into account.